Gambaran Kids Safety Park: Sebuah Studi Kualitatif Di RPTRA DKI Jakarta - Saufika, Alka; Sari, Meliana (UIN Sultan Maulana Hasanudin Banten, 2024)
Playgrounds should ensure the safety of children playing in them. However, more than 200,000 cases of child injuries occur each year due to playground activities. This study aims to examine child safety aspects in Child-Friendly Integrated Public Spaces (RPTRA) playgrounds using a descriptive qualitative method with a case study approach. A total of 10 informants were selected through purposive sampling. Data were collected through interviews, observations, and document reviews, then analyzed using thematic techniques. The findings reveal that RPTRA playgrounds face challenges in management and environment, such as the lack of specific budgets for playground management, absence of written Standard Operating Procedures (SOPs) for play equipment use, and limited supervision of children. Additionally, play equipment condition and playground layout are inadequate. This study recommends establishing a dedicated playground budget, improving supervision, and creating written SOPs for play equipment to enhance child safety in playgrounds.